STEAM (Science, Technology, Engineering, Arts and Mathematics) Learning in 21st Century Innovative Learning to Support Student Competencies in Science Subjects in Elementary Schools - Nita, B. Nuraulia Rahmanita; Fatonah, Siti (Sunan Kalijaga International Journal on Islamic Educational Research, 2023)
The 21st century is also known as the age of knowledge, which is an alternative effort to meet the needs of life in a variety of more knowledge-based contexts. One of the demands of 21st century learning is the integration of technology as a learning medium to develop learning skills. Innovative learning is a learning program that directly solves problems facing the classroom based on classroom conditions. One of the advances in education in Indonesia that is proven to develop humans who are able to build a science and technology-based economy is STEAM (Science, Technology, Engineering, Arts and Mathematics) learning. This research is a descriptive qualitative research that aims to obtain information about innovative learning in science subjects carried out in Madrasah Ibtidaiyah Negeri 3 Mataram. Data collection techniques are carried out by triangulation (combined), data analysis is inductive / qualitative. The subject of the study.